A novel design of low-voltage low-loss K-band RF-MEMS capacitive switch - Ma, Li-Ya; Soin, Norhayati; Nordin, Anis Nurashikin (IEEE, 2018)
This paper presents a novel design and analysis of capacitive radio frequency (RF) micro-electromechanical system (MEMS) switch. The RF-MEMS switch is actuated by electrostatic force with low-actuation voltage of 2.9V while it can be operated in a robust condition with maximum von Mises stress of 13.208 MPa which is less than aluminum’s yield stress. By finite-element-modeling (FEM) simulations, at switch-on state, insertion loss and reflection loss of the proposed RF-MEMS switch is obtained as -0.8023dB and -7.983dB, respectively; and at switch-off state, isolation and return loss is -22.45dB and - 0.8666dB, respectively. In order to improve the switch-on reflection loss to meet design specifications, two short high- impedance sections of transmission line have been calculated and added to the RF-MEMS switch. Then the reflection coefficient at switch-on state has been increased by 78.13% to -14.22dB which is less than -10dB while the insertion loss, isolation and return loss are all improved by 66.54%, 13.36% and 11.65%, respectively, with 65ohm high-impedance lines. The RF-MEMS switch’s actuation time of 27μs is obtained. A detail comparison among the proposed RF-MEMS switch and other state-of-the-art designs has been summarized in the end.